Diketopyrrolopyrrole-based fluorescence probes for the imaging of lysosomal Zn2+ and identification of prostate cancer in human tissue. Issue 22 (13th May 2019) - Du, Chenchen; Fu, Shibo; Wang, Xiaohua; Sedgwick, Adam C.; Zhen, Wei; Li, Minjie; Li, Xinqiang; Zhou, Juan; Wang, Zhong; Wang, Hongyu; Sessler, Jonathan L.
Abstract : Diketopyrrolopyrrole-based fluorescent probes have been developed for the detection of low pH and Zn 2+ in an AND logic fashion. They can discriminate between cancerous and healthy prostate tissue. Abstract : A series of diketopyrrolopyrrole-based fluorescent probes (DPP-C2, LysoDPP-C2, LysoDPP-C3, andLysoDPP-C4 ) have been developed for the detection of low pH and Zn 2+ in an AND logic fashion. The chelation of Zn 2+ or the protonation of a morpholine moiety within these probes results in a partial increase in the fluorescence intensity, an effect ascribed to suppression of one possible photo-induced electron transfer (PET) pathway. In contrast, a large increase in the observed fluorescence intensity is observed at low pH and in the presence of Zn 2+ ; this is rationalized in terms of both possible PET pathways within the probes being blocked. Job plots, fluorescence titration curves, and isothermal titration calorimetry proved consistent with a 1 : 1 Zn 2+ complexation stoichiometry. Each probe demonstrated an excellent selectivity towards Zn 2+ and the resulting Zn 2+ complexes demonstrated pH sensitivity over the 3.5–9 pH range. Fluorescence imaging experiments confirmed thatLysoDPP-C4 was capable of imaging lysosomal Zn 2+ in live cells. Little evidence of cytotoxicity was seen.LysoDPP-C4 was successfully applied to the bioimaging of nude mice, wherein it was shown capable of imaging the prostate. Histological studies using a human sample revealed thatLysoDPP-C4 can discriminate cancerous prostate tissue from healthy prostate tissue.